Designing Qur’an Experts in Indonesia: Feasibility Analysis of the Establishment of Ma’had Aly An-Nur 1 Malang Study Program of Qur’an and Qur’an Sciences - Ikhwanuddin, Mohammad; Khoiri, M. Nastainul; Idris, Muhammad Anwar; Rahmawati, Kharolina (Lembaga Pengembangan Pesantren dan Diniyah Provinsi Jawa Timur, 2024)
This research analyzes the readiness and feasibility of establishing Ma'had Aly An-Nur 1 Malang Quran and Quran Science Study Program by concentrating on Balāghat al-Quran (Rhetoric of Quran Studies) and looking at the expected design model of Quran experts. As an educational institution at the stratum one (S1) level, Ma'had Aly An-Nur 1 grows and originates from the characteristics of pesantren. This qualitative research explores data sources through structured interviews supported by literature data in the form of documents related to the establishment of Ma'had Aly An-Nur. This research is an important part of refining the terms and prerequisites for establishing Ma'had Aly in accordance with the Minister of Religion Regulation 32 of 2020 concerning Ma'had Aly. The results showed that Ma'had Aly Annur 1 Malang took the al-Quran wa Ulumuhu (Quran and Quran Science) Study Program with three arguments, namely the characteristics of the founders of the pesantren, the availability of the Quran memorization program, the need for a higher level of education after graduating from formal and diniyah schools while still affirming the distinctiveness of the pesantren. At the same time, the Takhassus of Balāghat al-Quran was chosen based on expertise in linguistic aspects and the need for proselytizers. The analysis results show the readiness and feasibility of establishing Ma'had Aly based on applicable regulations. The design of the Quran expert developed through 3 stages: pre-conditions, strengthening Quranic knowledge, and internalizing Quranic rhetoric. Supported by a curriculum structure consisting of 3 groups (basic, main, and supporting), Quran experts are designed to become qāri (readers), balīgh (rhetoricians), and dā'ī (preachers).